Incomplete footprint coverage under tension in repair of isolated supraspinatus full-thickness tear - Tae-Hwan Yoon (Nature Portfolio, 2021)
Abstract Although it is well known that repairing large or massive tears under tension may have an adverse effect on healing of the repaired tendons, only few studies have addressed this issue in medium-sized isolated supraspinatus full-thickness tear. The purpose of this study was to compare the clinical outcomes and structural integrity of arthroscopic rotator cuff repair with tension versus without it. This study retrospectively investigated 90 patients who underwent arthroscopic repair in a single-row for medium-sized isolated supraspinatus full-thickness tear. The patients were assigned to either repaired under tension (Group A, n = 38) or repaired without tension (Group B, n = 52) groups. Functional outcomes were assessed using the patient reported subjective values and the active range of motion (ROM). Postoperative radiographic evaluation was performed 6 months after the surgery to assess the structural integrity of the repaired tendons. Changes in the subjective shoulder scores from initial to 2 years after surgery showed no statistical significance between the two groups. The ROMs measured at initial and 2 years after surgery also showed no statistical difference between the two groups. Postoperative radiological evaluations found a significantly higher re-tear rate in Group A (28.9%, 11/38) than in Group B (9.6%, 5/52). The torn cuff tendons that were repaired under tension as retraction with limited mobility had significantly higher re-tear rate despite having immobilized for 6 weeks after surgery, but their clinical outcomes showed no significant difference from the outcomes of repaired tendons without tension.